Authentic Material and Interactive Activities in EFL Classroom - Arianie, Masita (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Abstract Actively engaging EFL learners in the classroom will help them think more deeply about the course content, bring additional energy to the classroom, and help identify the extent to which they may be struggling with the material. Yet, some teachers of English are having problem to engage students’ attention. Incorparating authentic material and interactive activities such as jigsaw reading and group discussion can be alternative ways to deliver the materials.The purpose of this paper is to highlight interactive activities which can motivate students and increase their interest in leaning English in EFL classroom. Keyword: authentic material, interactive activities and EFL classroom